Alternatif Pengobatan Hipertensi dalam Program Pengabdian Masyarakat STIKES Nasional di Desa Kwarasan, Grogol, Sukoharjo - Novena Yety Lindawati; Danie Nugroho; Geffa Yusinda Ardanaputri; Maria Oktafiani Ari Saputri; Mohollana Mohollana; Rika Triastuti; Sari Murdianningsih (Universitas Muhammadiyah Semarang, 2023)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest, calm. Treatment of hypertension can use medicinal plants, namely bay leaves and soursop leaves. Bay leaves and soursop leaves have antioxidant activity that can counteract free radicals so that they can lower blood pressure, while bay leaves themselves contain flavonoids that can reduce the risk of cardiovascular disease. This activity program uses the method of giving local seminars and workshops directly to the PKK group in Kwarasan Village, Grogol District, Sukoharjo Regency. The results of real work lecture program showed an increase in participants' knowledge which was evaluated through an average increase in the pretest score from 86 to 94 during the posttest as well as an increase in the skills of participants in workshop activities.